Interaction of Bacillus thuringiensis Cry1 and Vip3A proteins with Spodoptera frugiperda midgut binding sites - Sena, Janete A. D. [UNESP]; Hernández-Rodríguez, Carmen Sara; Ferré, Juan (American Society for Microbiology, 2009)
Vip3Aa, Vip3Af, Cry1Ab, and Cry1Fa were tested for their toxicities and binding interactions. Vip3A proteins were more toxic than Cry1 proteins. Binding assays showed independent specific binding sites for Cry1 and Vip3A proteins. Cry1Ab and Cry1Fa competed for the same binding sites, whereas Vip3Aa competed for those of Vip3Af. Copyright © 2009, American Society for Microbiology. All Rights Reserved.
Keywords: Bacillus thuringiensis; Binding assays; Binding interactions; Specific bindings; Spodoptera frugiperda; Bacteriology; Binding energy; Proteins; Binding sites; Bacillus thuringiensis toxin; bacterial toxin; Cry1Ab toxin; cry1fa protein; unclassified drug; vip3aa protein; vip3af protein; bacterium; caterpillar; protein; toxicity; bacterial strain; binding site; bioassay; Lepidoptera; midgut; nonhuman; protein analysis; protein expression; protein protein interaction; Animals; Bacterial Proteins; Endotoxins; Gastrointestinal Tract; Hemolysin Proteins; Larva; Lethal Dose 50; Protein Binding; Spodoptera